2013
DOI: 10.1002/phar.1297
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Prognosis, and Treatment of Resistant Hypertension

Abstract: Resistant hypertension is a common clinical problem, which, until recently, has received little attention in the medical literature. With this increased attention has come a considerably better understanding of disease epidemiology, prognosis, and treatment, yet much remains unknown. Current data suggest that the prevalence of resistant hypertension has been increasing in recent decades, a concerning finding given that resistant hypertension appears to be associated with a poorer prognosis than nonresistant hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 94 publications
1
8
0
1
Order By: Relevance
“…more severe or prolonged elevations in BP) over time compared with patients with nonresistant HTN, and res-HTN is reflective of adverse processes (e.g. increased renin–angiotensin system stimulation and aldosterone production, increased arterial stiffness, atherosclerotic disease) that have been linked with increased cardiovascular risk [1,5]. The latter hypothesis, in particular, may be favored by several recent lines of evidence from our study and others.…”
Section: Discussionsupporting
confidence: 50%
“…more severe or prolonged elevations in BP) over time compared with patients with nonresistant HTN, and res-HTN is reflective of adverse processes (e.g. increased renin–angiotensin system stimulation and aldosterone production, increased arterial stiffness, atherosclerotic disease) that have been linked with increased cardiovascular risk [1,5]. The latter hypothesis, in particular, may be favored by several recent lines of evidence from our study and others.…”
Section: Discussionsupporting
confidence: 50%
“…2-10 According to data from the National Health and Nutrition Examination Survey (NHANES), the prevalence of TRH appears to have more than doubled over the past quarter-century from 8.8% in 1988-1994 to 20.7% in 2005-2008. 11,12 Although the mechanisms underlying TRH development have not been elucidated, likely contributors include poor medication adherence, suboptimal antihypertensive regimens, obesity, alcohol consumption, high sodium intake, and concomitant use of medications that promote sodium retention or otherwise decrease antihypertensive efficacy. 12 Importantly, many of these contributing factors are modifiable, offering the potential for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Although the mechanisms underlying TRH development have not been elucidated, likely contributors include poor medication adherence, suboptimal antihypertensive regimens, obesity, alcohol consumption, high sodium intake, and concomitant use of medications that promote sodium retention or otherwise decrease antihypertensive efficacy. 12 Importantly, many of these contributing factors are modifiable, offering the potential for intervention.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Moreover, the prevalence of TRH seems to be increasing in the United States, highlighting the importance in addressing this rising health care problem. 6,7 Previous studies have shown that TRH is associated with worse health-related quality of life 8 and increased risk of cardiovascular outcomes and mortality relative to nonresistant hypertension. 3,5,9,10 In 2008, the American Heart Association (AHA) published a scientific statement identifying specific management strategies for patients with TRH, including promoting use of long-acting thiazide diuretics (eg, chlorthalidone and indapamide), addition of aldosterone receptor antagonists to the existing regimens, and withdrawal of potentially interfering medications (eg, nonsteroidal anti-inflammatory drugs) 11 ; these recommendations have been largely echoed elsewhere.…”
mentioning
confidence: 99%